(untitled) (European Journal of Teaching and Education, 2020)
The work presented in this paper is related to the use of the two-stage examination assessment to promote collaborative learning that has an impact on students’ engagement, learning and performance. It is an initiative to support Student Success project at Kent University. The project aims to reduce the attainment gap of various cohorts of students and enhance their academic performance. This paper presents the analysis and results obtained by applying the 2-stage examination assessment in a second-year undergraduate computer science module entitled Software Engineering Process. The 2-stage examination used in this study has proven that effective learning can take place when students work collaboratively. The data used for the analysis is students’ overall performance in the module and also the data collected by distributing a questionnaire to students at the end of the academic term in addition to online-survey conducted during the final exam preparation period. Students’ performance of the targeted module has been recorded, analysed and contrasted with the previous year cohort. In addition, students’ feedback related to their learning experience is recorded and anlaysed. As per the students’ performance, questionnaire and survey analysis results, one can consider that the 2-stage examination is a unique assessment, beneficial and very useful for final examination preparation.